The split stitch anchor: a technique to minimize suture material at wound ends - Duncumb, Joseph W.; Aithie, Joanna M. S.; Rehman, Haroon (International Surgery Journal, 2026)
Non-absorbable suture material can cause local irritation, connective tissue reaction and adhesions. This can lead to infection such as a stitch abscess, which may necessitate further surgical intervention. We describe a split stitch anchor technique to minimise excess suture material at wound ends with the aim of reducing infection risk.